Initial Teacher Training in Social Studies: A Case Study of a Private University in the Southern Region of Costa Rica - Arce Bolaños, Alejandro (2025)
This article presents the data from a case study on initial teacher training in a Costa Rican university. For the analysis, we started from the study category of Initial Teacher Training, which is understood as a line of research in the didactics of history for decision-making and reflection in practice (Añahual and Jara, 2021). The methodological strategy corresponds to a text analysis matrix for the interpretation of the components of the official curriculum, as well as open coding and triangulation of curricular documents. It is concluded that the initial training model transitions between the categories of the technical and practical curriculum, but is mostly technical, in that a model predominates over the teaching of traditional Social Studies.